The Funambulist Pamphlets 4: Legal Theory - Lambert, Léopold (punctum books, 2013)
The Funambulist Pamphlets is a series of small books archiving articles published on The Funambulist, collected according to specific themes. These volumes propose a different articulation of texts than the usual chronological one. The eleven volumes are respectively dedicated to Spinoza, Foucault, Deleuze, Legal Theory, Occupy Wall Street, Palestine, Cruel Designs, Arakawa + Madeline Gins, Science Fiction, Literature, and Cinema. The Funambulist Pamphlets is published as part of the Documents Initiative imprint of the Center for Transformative Media, Parsons The New School for Design, a transdisciplinary media research initiative bridging design and the social sciences, and dedicated to the exploration of the transformative potential of emerging technologies upon the foundational practices of everyday life across a range of settings.